EVALUATION OF THE EFFECT OF IMPLEMENTING DIGITAL TECHNOLOGY IN THE ACCOUNTING PROCESS ON THE EFFICIENCY AND ACCURACY OF FINANCIAL REPORTS - Indriyani Indriyani; Hendra Prasetyo; Masthuroh Masthuroh (Adisam Publisher, 2025)
This research aims to evaluate the effect of applying digital technology in the accounting process on the efficiency and accuracy of financial reports through a systematic literature review approach. Along with the development of information technology, various digital innovations such as Enterprise Resource Planning (ERP), Robotic Process Automation (RPA), Artificial Intelligence (AI), and blockchain have been adopted by companies to speed up accounting processes and increase the reliability of financial data. This study analyzes more than 30 scientific sources from various academic databases, using thematic analysis techniques to identify general trends, dominant technologies, and relevant industry context. The study results show that digital technology is able to increase efficiency through automation and process integration, as well as increase accuracy through reducing manual errors and real-time reporting capabilities. However, the success of implementation is greatly influenced by the quality of input data, organizational readiness, and human resource support. These findings provide theoretical contributions to the accounting information systems literature, as well as practical implications for companies and policy makers in designing effective and sustainable digitalization strategies.